The financial crisis of 2008 in fixed income markets - Gerald P. Dwyer; Paula Tkac (Federal Reserve Bank of Atlanta, 2009)
We explore how a relatively small amount of heterogeneous securities created turmoil in financial markets in much of the world in 2007 and 2008. The drivers of the financial turmoil and the financial crisis of 2008 were heterogeneous securities that were hard to value. These securities created concerns about counterparty risk and ultimately created substantial uncertainty. The problems spread in ways that were hard to see in advance. The run on prime money market funds in September 2008 and the effects on commercial paper were an important aspect of the crisis itself and are discussed in some detail.
Keywords: G01; G21; G23; G28; 330; financial crisis; contagion; collateralized debt obligations; ABX; money market funds; Finanzmarktkrise; Ansteckungseffekt; Geldmarktfonds; Asset-backed security; Commercial Paper; International